Thophic State of Bakuok Lake based on Phytoplankton in Aursati Village Tambang District Kampar Regency Riau Province - Merlin Evan Olivia Hutauruk; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstrak Many activities in the Bakuok Lake contribute the input of organic and anorganic matter that affects the nutrient concentration and increasing the growth of phytoplankton. A research has been conducted in June-July 2019. There were three sampling points, in the inlet, in the middle of the lake, and in the surface (0,15 m) and 2 Secchi depth (1,74 m). Samplings were conducted 3 times, once/week. Water quality parameters measured were temperature, transparency, depth, pH, dissolved oxygen, CO2, nitrate and phosphate.Results shown that there were 33 species of phytoplankton that were belonged to 7 classes, namely Chlorophyceae (15 spesies), Cyanophyceae (2 spesies), Bacillariaphyceae (5 spesies), Euglenophyceae (3 spesies), Zygnematophyceae (5 spesies), Trebouxiophyceae(2 spesies), and Cryptophyceae (1 spesies).The phytoplankton abundance of the Bakuok Lake was 89.689-100.491 cells/L. The most common type ofphytoplankton presentwasAnkistrodesmus falcatus. Water quality parameters values were as follow, temperature was 29-310C, depth was 4-6 m, pH was 5, dissolved oxygen was 6.57-7.57 mg/L, CO2 was 9.37-13.86 mg/L, nitrate was 0.0190-0.0333 mg/L and phosphate was 0.0354-0.0575 mg/L. Based on the type and abundance of phytoplankton, it can be concluded that the Bakuok Lake can be categorized as mesotrophic. Keywords :Oxbow Lake, Water Quality, Ankistrodesmus falcatus, Mesotrophic